Atmosphere - MDPI (MDPI, 2026)
Atmosphere is an international, peer-reviewed, open access journal of scientific studies related to the atmosphere, published monthly online by MDPI. The Italian Aerosol Society (IAS) and Working Group of Air Quality in European Citizen Science Association (ECSA) are affiliated with Atmosphere and their members receive a discount on the article processing charges.
Keywords: Ciencias atmosféricas; Revistas depredadoras; Predatory journals